Child Health: Is It Really Assisted Reproductive Technology that We Need to Be Concerned About? - Yeung, Edwina H.; Kim, Keewan; Purdue-Smithe, Alexandra; Bell, Griffith; Zolton, Jessica; Ghassabian, Akhgar; Vafai, Yassaman; Robinson, Sonia L.; Mumford, Sunni L. (Seminars in Reproductive Medicine, 2018)
Concerns remain about the health of children conceived by infertility treatment. Studies to date have predominantly not identified substantial long-term health effects after accounting for plurality, which is reassuring given the increasing numbers of children conceived by infertility treatment worldwide. However, as technological advances in treatment arise, ongoing studies remain critical for monitoring health effects. To study whether the techniques used in infertility treatment cause health differences, however, remains challenging due to identification of an appropriate comparison group, heterogeneous treatment, and confounding by the underlying causes of infertility. In fact, the factors that are associated with underlying infertility, including parental obesity and other specific male and female factors, may be important independent factors to consider. This review will summarize key methodological considerations in studying children conceived by infertility treatment including the evidence of associations between underlying infertility factors and child health.
Keywords: child health; IVF; confounding; epidemiology